2021
DOI: 10.1080/1369118x.2021.1933563
|View full text |Cite
|
Sign up to set email alerts
|

Gauging reference and source bias over time: how Russia’s partially state-controlled search engine Yandex mediated an anti-regime protest event

Abstract: Massive efforts have been dedicated to studying political search engine bias in democratic contexts, and a growing body of literature has scrutinized search engine censorship in authoritarian China. By contrast, very little is known still about political search engine bias within Russia's slightly more open authoritarian media system. In order to fill in this gap, this study asks: How has Russia's leading partially state-controlled search engine Yandex mediated a large-scale anti-regime protest event (anti-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Several audit studies have been conducted where researchers query terms on multiple search engines and compare the rankings of relevant results. In one audit, Kravets and Toepfl (2021) found that Yandex returned far fewer websites than Google with information on anti-regime Russian protests. An additional cross-country audit found Google to be effective at suppressing pro-Kremlin content in five countries (Toepfl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several audit studies have been conducted where researchers query terms on multiple search engines and compare the rankings of relevant results. In one audit, Kravets and Toepfl (2021) found that Yandex returned far fewer websites than Google with information on anti-regime Russian protests. An additional cross-country audit found Google to be effective at suppressing pro-Kremlin content in five countries (Toepfl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In one audit, Kravets and Toepfl (2021) found that Yandex returned far fewer websites than Google with information on anti-regime Russian protests. An additional cross-country audit found Google to be effective at suppressing pro-Kremlin content in five countries (Toepfl et al, 2021). Additionally, one audit compared Google and Yandex rankings of content related to Alexei Navalny and found that Google promoted opposition sources more frequently than Yandex (Makhortykh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since Yandex is a Russian domestic corporation, it is generally thought to be more responsive to government pressure (Daucé & Loveluck, 2021) while Google is seen by many Russian NGOs as a protector of civil liberties (Bronnikova & Zaytseva, 2021) Compared with Google, Yandex was more intensively targeted by Russian regulatory mechanisms (Wijermars, 2021) and demonstrated more politically biased performance during periods of political contention (Kravets & Toepfl, 2021). However, the Russian authorities also put increasing pressure on Google as demonstrated by the growing number of requests for removing results from its search, particularly since the second half of 2020 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The situation is further complicated by the tendency of some search engines (e.g. Yandex, a Russian search engine) to amplify pro-Kremlin narratives (Kravets and Toepfl, 2021), which can have implications for their curation of memory-related information. To investigate the performance of search engines under these circumstances, we conducted a comparative audit of search outputs for the query 'Holodomor' in Latin and Cyrillic script for four major search engines: Bing, DuckDuckGo, Google, and Yandex.…”
Section: Introductionmentioning
confidence: 99%